2005
DOI: 10.1007/s11107-004-5583-6
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Hybrid-Switching Optical Router for IP over WDM Integration

Abstract: Because pure electrical routers with their bandwidth limitations can hardly keep up with the tremendous traffic growth in the Internet, optical routers based on various optical switching techniques including optical wavelength switching (OWS), optical burst switching (OBS), and optical packet switching (OPS) have been suggested to cope with this problem. However, because OBS and OPS are both in their early experimental phase and OWS only provides coarse granularity switching, a hybrid-switching optical router … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In [8,9], NTT and Fujitsu demonstrated burst switching with GMPLS-based two-way signaling protocol, utilizing planar lightwave circuit (PLC) and MEMS switches. In [10], commercial PLC switches were adopted to construct a 1616 non-blocking switch matrix with a switching speed of less than 3 ms. OBS schemes with hybrid optical and electrical switching technologies have been investigated in the past [11]. A recent study demonstrated that a PLZT switch (lead lanthanum zirconate titanate, [12]) with shared wavelength conversion allowed variable-length 3.5 ns OBS.…”
Section: A Optical Switching Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In [8,9], NTT and Fujitsu demonstrated burst switching with GMPLS-based two-way signaling protocol, utilizing planar lightwave circuit (PLC) and MEMS switches. In [10], commercial PLC switches were adopted to construct a 1616 non-blocking switch matrix with a switching speed of less than 3 ms. OBS schemes with hybrid optical and electrical switching technologies have been investigated in the past [11]. A recent study demonstrated that a PLZT switch (lead lanthanum zirconate titanate, [12]) with shared wavelength conversion allowed variable-length 3.5 ns OBS.…”
Section: A Optical Switching Technologiesmentioning
confidence: 99%
“…Thus, according to Yoo et al in [5], Table I identifies possible switch fabrics for the development of a multi-granular switch. A detailed discussion based on the attributes mentioned above can be found in Wei et al [11] and Papadimitriou et al [6]. Clearly, one of the most appropriate slow switching technologies is the optical MEMS switch, since it is already a mature technology under production and because of the high dimensions available at low cost [14,15].…”
Section: A Optical Switching Technologiesmentioning
confidence: 99%